2017
DOI: 10.2196/mhealth.7689
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health in Oncology: A Patient Survey About App-Assisted Cancer Care

Abstract: BackgroundIn the last decade, the health care sector has been enriched by numerous innovations such as apps and connected devices that assist users in weight reduction and diabetes management. However, only a few native apps in the oncological context exist, which support patients during treatment and aftercare.ObjectiveThe objective of this study was to analyze patients’ acceptance regarding app use and to investigate the functions of an oncological app that are most required, and the primary reasons for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 15 publications
11
97
2
4
Order By: Relevance
“…Traditionally, patients have tried to physically obtain medical information from ordinary health professionals (doctors, pharmacists and nurses). However, the expansion and generalization of the use of ICTs has implied a radical change in how we obtain information about health and manage diseases [3,4,5,11,12]. While health professionals continue to be the main source of information about diseases (the first option of 75.5% (462/611) of patients is to turn to their doctor), 61.3% (375/611) (55% in the study by An LC et al [13]) also resort to the Internet for information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, patients have tried to physically obtain medical information from ordinary health professionals (doctors, pharmacists and nurses). However, the expansion and generalization of the use of ICTs has implied a radical change in how we obtain information about health and manage diseases [3,4,5,11,12]. While health professionals continue to be the main source of information about diseases (the first option of 75.5% (462/611) of patients is to turn to their doctor), 61.3% (375/611) (55% in the study by An LC et al [13]) also resort to the Internet for information.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the questionnaire considered the model form created by ONTSI [4] and incorporated advice from a management consultancy firm specializing in process design, implementation, and improvement. With respect to the types of question, 28 comprised dichotomous (2,3,6,12,18,20,22,27), with true/false response options, or polytomous (questions 4-5, 7-10, 11, 13-17, 19, 21, 23-26) categorical variables. Ten patients completed a draft paper questionnaire to validate the fact that it was well understood.…”
Section: Methodsmentioning
confidence: 99%
“…A survey among 108 oncologists and nurses reported that more than 80% of health care providers deemed app-based PRO reporting as useful as part of complimentary oncological surveillance [24]. Patients seemed slightly more reluctant to share their medical data with between half and two thirds of patients willing to report PROs online [25,26]. Only few clinical factors seem to influence the willingness of patients to use mobile device-based PRO reporting, including a younger age and a reduced performance status while gender, tumour stage, histology and type of treatment did not have any significant effects [26].…”
Section: Tackling the Great Unknown: Capability Versus Willingnessmentioning
confidence: 99%
“…Beyond patient compliance, patient ability to access and use mobile technology may also pose a major challenge for mobile PRO reporting. The availability of mobile devices among cancer patients has been reported to range between 70 and 80% [25,26]; however, this patient cohort contains a considerable percentage of elderly patients that may not have access to mobile technology. In order to accommodate these patients, web-based platforms and the recruitment of family members and relatives for the collection and reporting of PROs have been used as alternative means in prospective trials [4,8].…”
Section: Tackling the Great Unknown: Capability Versus Willingnessmentioning
confidence: 99%
“…The growing range of apps will also make it easier for the individual to understand at an earlier stage if a treatment is needed or not, which will also boost the chances for cost savings on unnecessary treatments - and will also provide a psychological boost for the individual, a reassurance that he or she retains some control of their own lives [28]. Education plays an important role here as well as the governance structures.…”
Section: Person-centric Healthcarementioning
confidence: 99%